2014
DOI: 10.3989/gya.122213
|View full text |Cite
|
Sign up to set email alerts
|

Virgin olive oil color and perceived quality among consumers in emerging olive-growing countries

Abstract: SUMMARY:Five virgin olive oil samples were evaluated by 122 consumers for their color acceptability and expected quality on 9-point structured scales. A description of the attributes expected in the different oils was obtained from the responding consumers by means of a check-all-that-apply questionnaire consisting of a list of 17 possible virgin olive oil attributes. Hierarchical cluster analysis led to the identification of two consumer clusters with distinct behavior. Whereas one consumer cluster attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The perspective of the German market has great potential for Croatian olive oils, since the surveyed consumers evaluated the regional and micro-localities of production highly in the context of Croatia as a country of production, similarly to the findings of [10,13], whereas country and region of production can be used in marketing strategies. For local Croatian farmers, the importance of local production for German consumers assures the sustainability of local production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perspective of the German market has great potential for Croatian olive oils, since the surveyed consumers evaluated the regional and micro-localities of production highly in the context of Croatia as a country of production, similarly to the findings of [10,13], whereas country and region of production can be used in marketing strategies. For local Croatian farmers, the importance of local production for German consumers assures the sustainability of local production.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the segmentation of [1] showed that the expert group gave more importance to intrinsic attributes compared to utilitarian and naïve consumers. Additionally, in Italy, two clusters were identified according to their preferences for color, flavor, and taste of olive oil [10], while consumers' knowledge about the meaning of organic olive oil was referred by [2]. In Spain, upper social groups and higher income groups were more aware of protected designation of geographical origin (PDO) labels [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in Spain showed that the dark yellow color of the Arequipa's olive oil was more appreciated by consumers in the Terragone region of Catalonia, whereas the dark green color was appreciated in Andalusia [7]. In Uruguay, the green and dark green colors are associated with more expensive, richly flavored and tasty oils [8], while the pale yellow color was considered as a sign of poor quality and associated with cheap products having a slighter taste, and are therefore the least acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…The term “by passing off inferior product” is directly but not exclusively related to Quality that is defined according to ISO 9000 normative as “the degree to which a set of inherent characteristics of an object fulfills requirements.” These requirements are not permanent as they change over time, which explains why the term quality is subjected to temporary variations in its meaning . For instance, consumer currently has a preference for virgin olive oils (VOO) with greener color as in general consumers thinks that the greener the oil, the most flavorful the oil …”
Section: Introductionmentioning
confidence: 99%